Contesting the foreshore : tourism, society, and politics on the coast - Boissevain, Jeremy; Selwyn, Tom (MARE publication series, 2004)
A collection of essays studying the rapid changes in coastal settlements due to the conflicting interests of traditional and new stakeholders.